1999
DOI: 10.1287/mnsc.45.7.1008
|View full text |Cite
|
Sign up to set email alerts
|

Information Technology Effects on Firm Performance as Measured by Tobin's q

Abstract: Despite increasing anecdotal evidence that information technology (IT) assets contribute to firm performance and future growth potential of firms, the empirical results relating IT investments to firm performance measures have been equivocal. However, the bulk of the studies have relied exclusively on accounting-based measures of firm performance, which largely tend to ignore IT's contribution to performance dimensions such as strategic flexibility and intangible value. In this paper, we use Tobin's q, a finan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
566
3
15

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 863 publications
(606 citation statements)
references
References 75 publications
22
566
3
15
Order By: Relevance
“…Positive and signi"cant relationships were found between certain investment measures and organizational performance. Similarly, Bharadwaj, Bharadwaj and Konsynski (1999) found evidence that IT investments had a positive association with Tobin's q value (a "nancial market-based measure of "rm performance).…”
Section: Positive (Or Mixed ) Relationshipmentioning
confidence: 96%
“…Positive and signi"cant relationships were found between certain investment measures and organizational performance. Similarly, Bharadwaj, Bharadwaj and Konsynski (1999) found evidence that IT investments had a positive association with Tobin's q value (a "nancial market-based measure of "rm performance).…”
Section: Positive (Or Mixed ) Relationshipmentioning
confidence: 96%
“…The obtained results in this empirical study would be identified with a group of previous literature as for example. Mukhopadhyay et al (1997) that state that ICT increases the quality, and this increase offers at the same time an increase in productivity, and Bharadwaj et al (1999) that state how some intangible values, coming from ICT investments have a tendency to improve the quality of products, services, and customer attention. Porter (2001) also stresses how the implementation of ICT in organizations improves the quality and the service differentiated to the customer and Pérez (2001) in a specific work on public transport affirms that the implementation of ICT in firms improves the quality of service.…”
Section: Figure 7 Results In the Estimations Of The Quality Indexmentioning
confidence: 99%
“…The following studies would support the results in the empirical study : Mukhopadhyay, Rajiv, and Srinivasan (1997) defend that ICT increases the quality of the service. Bharadwaj et al (1999) also show in an illustrative way, that some intangible values, coming from ICT investments, would have an impact in the improvement of some aspects: in the quality of products and services, in the relationship with the final customer. Porter (2001) stresses how the implementation of ICT improves the quality and service by promoting a differentiation in the customer.…”
Section: H2 the Implementation Of An Ita System Improves The Qualitymentioning
confidence: 91%
See 1 more Smart Citation
“…Although some empirical studies demonstrate a positive relationship between IT and success variables (Bharadwaj, Bharadwaj, and Konsynski, 1999;Brynjolfsson and Kemerer, 1996;Devaraj and Kohli, 2000;Dewan and Min, 1997;Mukhopadhyay, Rajiv, and Srinivasan, 1997) overall results are contradictive and result the so called "IT paradox" (Brynjolfsson, Hitt, and Yang, 2002).…”
Section: It Business Value and It Usagementioning
confidence: 99%